2016
DOI: 10.1111/2041-210x.12605
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of statistical methods and sampling designs for the assessment of microhabitat selection based on point data

Abstract: 1. Information on resource selection by a species is essential for understanding the species' ecology, distribution and requirements for survival. Research on habitat selection frequently relies on animal detection at point locations to determine which resource units are used. A variety of approaches and statistical tools can be employed for assessing selection based on habitat variables measured in those units. The aim of this work is to evaluate the reliability of common sampling designs and statistical meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…We then used a binomial generalized linear mixed model to assess which environmental factors influence the occupancy of crane flies in subterranean environments [57]. Their presence/absence was used as dependent variable, while the morphological and microclimatic features of cave sectors, along with depth, as independent variables; site and sector identity were used as random variables.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…We then used a binomial generalized linear mixed model to assess which environmental factors influence the occupancy of crane flies in subterranean environments [57]. Their presence/absence was used as dependent variable, while the morphological and microclimatic features of cave sectors, along with depth, as independent variables; site and sector identity were used as random variables.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…According to our design, the closure assumption was not met at this scale of analysis because animals likely moved from one trapping station to another during the sampling period. Although this leads to biased estimates of detectability and occupancy, Gorosito et al (2016) found that covariates affecting habitat selection can still be successfully identified. Therefore, abundance is not to be taken literally as such, but as a relative measure of the intensity of use.…”
Section: Statistical Analyses At Microhabitat Scalementioning
confidence: 99%
“…Although this bias was expected, individuals were not captured independently of the microhabitat characteristics surrounding the trap stations. Habitat selection results from trapping studies should be compared with that of free‐roaming animals, that are more costly. A study on habitat selection of R. norvegicus using spool‐and‐line technique in two of the study farms yielded very similar results .…”
Section: Discussionmentioning
confidence: 99%